The Ability of Staphylococcus aureus to Establish Biofilm on Acrylic, Plastic, and Metallic Denture Materials - Mohammed, Rafid Salih; Al-Mathkhury, Harith Jabbar Fahad (Iraqi Journal of Science, 2023)
Staphylococcus aureus is a common pathogenic agent due to its ability to cause various types of infections, ranging from mild skin infections to sever systemic diseases. One of the most virulence factors of this bacterium is its ability to from biofilms on solid surfaces by anchoring the planktonic cells and by producing a protective layer of extra polymeric substances. Biofilm formation is controlled through many genes. The most important ones are icaA and icaD. Dentures are prosthetic devices that are made of different materials to replace lost teeth. The aim of this study is to examine the ability of different types of denture materials to support the biofilm formation of S. aureus at phenotypic level by detecting bacterial growth on them using crystal violet and scanning electron microscope, as well as genotypic level through detection and estimation of gene icaA and icaD expression. Our findings showed that the denture materials do support biofilm formation and there is elevation in gene expression of icaA and icaD.